Analisis Otentisitas Pengalaman Wisatawan pada Virtual Event Suatu Sanggar Budaya di Saung Angklung Ujo - Adrian Agoes; Andhika Chandra Lesmana (Manajemen dan Pariwisata, 2023)
The digital technology that has been around us for a long time has had a significant impact on our lives today. Digital technology is prevalent in many sectors of life, such as entertainment, information search tools, and online shopping and purchasing. It is by far the best choice for society in general during the current pandemic. Saung Angklung Udjo is one of West Java's tourist attraction offering traditional Sundanese arts and culture. With the Covid-19 pandemic, SAU must innovate in order to help the government's agenda in controlling the virus's spread, thus to survive under present conditions. This research examines the authenticity of a tourist's experience after virtually participating in an event hosted by SAU. The study's findings suggest that a virtual show in general has not been able to complete the authenticity of the visitor experience in seeing a cultural performance. However, based on the kind of performances presented by SAU, tourists can still have a genuine experience, particularly in the dimension of Existential Authenticity. This means that, to some extent, the experience of viewing virtual performances offers a sense of authenticity to personal experience, but the experience is not perfect, particularly in the aspects of involvement and interactivity.